Development and manufacturing of a measurement apparatus for NC machine tools diagnosis by double shaft-hole bar (DSB) method. - Prakosa, Tri (Asean Engineering Journal)
Manufacturing industries rely mostly on machine tools. Product quality produced by these industries depends on machine tools quality used to machine the product. In order to determine the machine tools quality, measurement must be conducted by using measurement apparatus. One of the apparatus is DBB (double ball bar) system. Unfortunately, the price of commercial DBB is quite expensive. To solve the problem, a new measurement apparatus based on Double Shaft-Hole Bar (DSB) method has been developed. The new design uses two precision shaft-hole pairs, instead of two high precision balls, connected by an extension bar. The design resembles ISO 230-1 basic design with some modifications, according to developing countries manufacturing capability. Data acquisition for the measurement system consists of 1 um accuracy LVDT as a position sensor, amplifier, 14 Bit ADC and personal computer. The measurement apparatus capability is measured by comparing apple to apple with Renishaw ball bar system. The results show that an accuracy of 5 um can be reached in CCW direction. While, in CW direction the accuracy is about 22 um, due to mechanical clamping system stability, which needs further study. The system, apart from the computer, can be manufactured with a budget less than USD 1,500.